Shallow foundations : bearing capacity and settlement - Das, Braja M., 1941 (Boca Raton : CRC Press, 2017)
Following the popularity of the previous edition, Shallow Foundations: Bearing Capacity and Settlement, Third Edition, covers all the latest developments and approaches to shallow foundation engineering. In response to the high demand, it provides updated data and revised theories on the ultimate and allowable bearing capacities of shallow foundations. Additionally, it features the most recent developments regarding eccentric and inclined loading, the use of stone columns, settlement computations, and more. Example cases have been provided throughout each chapter to illustrate the theories presented.
Chapter 1. Introduction -- Chapter 2. Ultimate bearing capacity theories : centric vertical loading -- Chapter 3. Ultimate bearing capacity under inclined and eccentric loads -- Chapter 4. Special cases of shallow foundations -- Chapter 5. Settlement and allowable bearing capacity -- Chapter 6. Dynamic bearing capacity and settlement -- Chapter 7. Shallow foundations on reinforced soil -- Chapter 8. Uplift capacity of shallow foundations.
Keywords: Foundations; Settlement of structures; Soil mechanics